Civics Education Teaching Materials with Balinese Cultural Perspective for Enhancing Learning Achievement and Love of Balinese Culture Attitude at Elementary School - Adijaya, Made Aryawan (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
This study aimed at developing civics education teaching materials with Balinese cultural perspective. This study was development research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects of this research were a third-grade teacher and twenty-three third grade students. To measure the validity of the teaching materials an expert’s evaluation sheet was used and to evaluate the implementation of the civics materials teachers’ and students’ responses questionnaires were used. The results of of the study were: 1) one civics teaching material, seven lesson plans, and 7 student worksheets which have been developed with Balinese cultural perspective. The material that was developed was under the topic “Bangga Menjadi Anak Indonesia” (Proud to become Indonesian children). 2) This product has been validated by an expert in civics education, an instructional design expert, a Balinese culture expert, and an evaluation expert and an education expert, yielding CVR of 1.00 and CVI of 1.00, categorized as valid and feasible to be tried out. 3) This product has been tried out on a limited scale in the third grade and the result showed that the produce could enhance learning achievement of the students with the averages of 81.04, 86.83, and 90.22, in the first, second and third meetings respectively, and love of Balinese culture attitude of the students with the averages of 86.90, 88.46 and 91.42.